Dermoid cyst of the pancreas: a case report - Carla Kellen da Silva Menezes; Luciana Botinelly Mendonça Fujimoto; Leonardo Simão Coelho Guimarães; Silvana de Albuquerque Silva Damasceno; Jenifer Morais de Melo (Sociedade Brasileira de Patologia Clínica, 2013)
Dermoid cysts or mature cystic teratomas are mesenchymal neoplasms most commonly found in the ovaries, but which may occur in any location along the pathways of ectodermal cell migration. They are rarely seen in the pancreas, where they show a slight preference for the pancreatic head. We report a case of dermoid cyst of the pancreas in a 69-year-old male patient, discussing the epidemiology, clinical presentation, diagnosis and treatment of this neoplasm. Since preoperative diagnosis is difficult, given its rarity in this site, it is usually diagnosed by histopathology of the specimen.